2017
DOI: 10.1097/prs.0000000000003769
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and the Plastic Surgery Patient

Abstract: This study is the first to articulate the plastic surgery patient perspective regarding social media. The findings aim to help plastic surgeons maximize their influence on their target audience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 14 publications
4
93
0
6
Order By: Relevance
“…Of the procedures mostly likely to be requested as a result of social media influence were rhinoplasty, Botox and facelifts, suggesting that young people may be influenced to undergo cosmetic procedures by what they see online. Similarly, a study has shown that among cosmetic surgery patients, Facebook, YouTube and Instagram are high in use and engagement for information regarding procedures, such as practice information, before and-after photographs, and contests (Sorice et al 2017). However, despite the growing popularity in cosmetic procedures, the social and psychological factors that influence attitudes towards cosmetic surgery are yet to be fully explored.…”
Section: The Influence Of Social Media On Body Imagementioning
confidence: 99%
“…Of the procedures mostly likely to be requested as a result of social media influence were rhinoplasty, Botox and facelifts, suggesting that young people may be influenced to undergo cosmetic procedures by what they see online. Similarly, a study has shown that among cosmetic surgery patients, Facebook, YouTube and Instagram are high in use and engagement for information regarding procedures, such as practice information, before and-after photographs, and contests (Sorice et al 2017). However, despite the growing popularity in cosmetic procedures, the social and psychological factors that influence attitudes towards cosmetic surgery are yet to be fully explored.…”
Section: The Influence Of Social Media On Body Imagementioning
confidence: 99%
“…A prospective analysis of 300 posts in the 3 most popular global social media networks was performed. 15 A search for English written posts using the key phrase “Plastic Surgery” was conducted on Facebook and YouTube, and with the hashtag “#plastic_surgery” on Instagram during the second week of November 2017. Exclusion criteria included indecipherable posts, re-posts, and posts unrelated to plastic surgery.…”
Section: Methodsmentioning
confidence: 99%
“…The first 100 recent posts on each of the 3 social media platforms that answered the criteria above were selected for a total of 300 posts, a method chosen after consulting a social media expert, and which was similarly applied in other recent studies. 5,8,15 Each post was assessed for the following parameters: author identity, subject (self-promotion, educational, commercial, and personal posts), “social media currency” (likes, shares, comments), and for the use of special media (videos, photographs, etc.) or viral subjects (reality stars or shaming).…”
Section: Methodsmentioning
confidence: 99%
“…Hage et al report that tweets related to IR have more than quadrupled over a three year period [14]. Other specialties have long embraced social media for the purposes of patient outreach, education, and advertising [15,16]. While social media can be used as a tool to connect with others, IRs and other medical providers should receive training on how to utilize this media without breaking HIPAA barriers before creating their respective pages.…”
Section: Utilize Social Mediamentioning
confidence: 99%